Diode laser excision of pyogenic granuloma on an uncommon oral site: A case report - Aggarwal, Neha; Sangwan, Aditi; Devi , Anju (Journal of Orofacial Research, 2025)
Pyogenic granuloma is a benign, vascular growth that typically results from factors like chronic irritation, trauma, or hormonal changes. While it is most commonly found on the gingiva, its appearance on the buccal mucosa is rare, which can make diagnosis more complex. A 56 year old female presented with a gradually enlarging, painless lesion on her right buccal mucosa that had been present for three months. Clinical examination revealed a firm, red, sessile mass that bled upon manipulation. Based on these findings, a diagnosis of pyogenic granuloma was made, with hemangioma considered as a differential diagnosis. The lesion was excised using a diode laser under local anesthesia. The procedure was performed with minimal bleeding, and the surgical site was well illuminated, making the excision precise. The patient experienced no complications during the healing process, and at the 12 month follow up, the lesion had fully healed without any signs of recurrence.